Power compensation for vector-based current control of a modular multilevel converter (MMC) based STATCOM - Lawan, Abdurrahman Umar; Babani, S.; Abdulkarim, A.; Shehu, G. S.; Jibril M, Y.; Madugu, I. S. (Institute of Advanced Engineering and Science, 2019)
This paper studies the suitability of a vector based current control which is mostly employed for its faster response in the reactive current applications of static compnesators (STATCOMs). The current control is mostly achieved using proportional-integral (PI) controllers because of the advantage of their good tracking and small variations. However, due to the dependency of PI controllers on the modular multilevel converter (MMC) system dynamics, performance variations arise during steady-state STATCOM non-ideal operations. This paper presents an improved MMC based STATCOM control with a d-q compensation algorithm added to the vector based current control. The algorithm is derived to tackle the effects of the dynamics of the MMC and the STATCOM ideal variations without the use of any additional controller. The control is achieved by providing a power compensation in the d,q-axis which injects currents at the input of the PI controllers in order to improve the steady-state performance of the STATCOM control.